Test de consistencia termodinámica para equilibrios líquido-vapor isobáricos de mezclas binarias (2017)
The present article gives the Thermodynamic Consistency evaluation of the binary system benzene-2-propapol vapor liquid equilibrium isobaric data points established and published by Nagata on the article “Vapor Liquid Equilibrium Data” on 1965. The consistency test realized was proposed by Fredenslud 1977 well known as “point-test” developed from the Gibbs-Duhem equation, the Gibbs function chosen was the Redlich-Kister polynomial expansion minimized by GaussNewton algorithm modified by Legendre polynomials, the result was thermodynamic consistency of these data points.